Egypt's domestic natural gas industry - Alami, R (Oxford Institute for Energy Studies, 2006)
In just 15 years, Egypt moved from a dependency on oil to using gas for meeting almost half of its energy needs. This paper follows the development of this domestic gas market. It finds that demand creation was linked to upward revisions in reserve availability, but was also driven by domestic concerns about pollution and international finance which supported conversion to gas. Today, gas penetration in power generation is almost complete, and is substantive in heavy and large industries. Despite tripling over the last 10 years, the number of households connected to the gas grid is still only at 18% of households. Private distribution companies, established as part of on-going macro-economic reforms, have been key to delivering this success. Lastly, Egypt is now the world’s eighth largest CNG user, with 50 stations currently operational. The development of this market was effectively financed by sustained and substantial public investments. Related costs have still not been fully amortised, featuring as outstanding debts to the public bodies involved. While these investments have given Egypt a relatively developed gas chain from well head to delivery point, this chain is at best an emerging market. Prices are still centrally controlled, fuel delivery is still a bundled service, and private participation remains limited to a few private distribution companies. Establishing the regulatory and legislative bases of the natural gas market, including a regulator, is very much work in progress.